2003
DOI: 10.1172/jci200317864
|View full text |Cite
|
Sign up to set email alerts
|

P2Y12 regulates platelet adhesion/activation, thrombus growth, and thrombus stability in injured arteries

Abstract: The critical role for ADP in arterial thrombogenesis was established by the clinical success of P2Y12 antagonists, currently used at doses that block 40–50% of the P2Y12 on platelets. This study was designed to determine the role of P2Y12 in platelet thrombosis and how its complete absence affects the thrombotic process. P2Y12-null mice were generated by a gene-targeting strategy. Using an in vivo mesenteric artery injury model and real-time continuous analysis of the thrombotic process, we observed that the t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
99
2

Year Published

2004
2004
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 100 publications
(109 citation statements)
references
References 37 publications
8
99
2
Order By: Relevance
“…The tools available for the analysis of P2Y 12 receptor function have facilitated characterization of the implications of P2Y 12 antagonism, though the studies performed thus far also raise more questions. The differences in embolization between homozygous and heterozygous mice observed by Andre et al (16) raise several important questions. Would complete blockade of the P2Y 12 receptor be a better therapeutic goal, and would it be more beneficial than clopidogrel because of abolished receptor function?…”
Section: In Vivo Analysis Of Thrombus Growth and Stabilitymentioning
confidence: 95%
See 1 more Smart Citation
“…The tools available for the analysis of P2Y 12 receptor function have facilitated characterization of the implications of P2Y 12 antagonism, though the studies performed thus far also raise more questions. The differences in embolization between homozygous and heterozygous mice observed by Andre et al (16) raise several important questions. Would complete blockade of the P2Y 12 receptor be a better therapeutic goal, and would it be more beneficial than clopidogrel because of abolished receptor function?…”
Section: In Vivo Analysis Of Thrombus Growth and Stabilitymentioning
confidence: 95%
“…Andre et al (16) used several approaches to explore the effects of P2Y 12 receptor deficiency on thrombus formation. FeCl 3 -induced vessel wall injury of the mouse mesenteric artery resulted in occlusion of the wild-type mouse vessel; however, the P2Y 12 -deficient mouse vessel remained unoccluded in eight out of nine mice (16). The appearance of the first thrombus was delayed and only small "unstable" thrombi formed in P2Y 12 -/-mice (16).…”
Section: In Vivo Analysis Of Thrombus Growth and Stabilitymentioning
confidence: 99%
“…Consistent with observations in patients deficient in the P2Y 12 receptor, mice lacking the P2Y 12 receptor have increased tail bleeding times (19,36,40,41). However, heterozygous mice show little or no change in bleeding times (16). It is currently unclear why a 50% decrease in the population of functional P2Y 12 receptors, either following clopidogrel treatment or in humans heterozygous for the P2Y 12 receptor, prolongs bleeding time, while heterozygous mice show little change in bleeding time ( Table 1).…”
Section: Bleeding Timesmentioning
confidence: 99%
“…Treatment with AR-C69931MX also decreased the reocclusion rate and improved myocardial tissue perfusion in a canine model of coronary electrolytic injury (53). Andre et al (16) used several approaches to explore the effects of P2Y 12 receptor deficiency on thrombus formation. FeCl 3 -induced vessel wall injury of the mouse mesenteric artery resulted in occlusion of the wild-type mouse vessel; however, the P2Y 12 -deficient mouse vessel remained unoccluded in eight out of nine mice (16).…”
Section: In Vivo Analysis Of Thrombus Growth and Stabilitymentioning
confidence: 99%
“…A second receptor for ADP on platelets, P2Y12, is coupled primarily to the G i family member, G i2 (4,33). Studies showing that platelets lacking G i2 or the P2Y12 receptor have reduced responses to thrombin (2,4,34) and that blockade of P2Y12 destabilized platelet aggregates (35) raised the possibility that thrombin-mediated Akt phosphorylation might be mediated by ADP release. Our studies of Akt phosphorylation in Gα i2 -versus Gα q -null platelets showed that thrombin can stimulate Akt phosphorylation under conditions where ADP cannot, suggesting that platelets stimulated with thrombin (or U46619) do not require secreted ADP to activate Akt, although ADP can amplify Akt activation by stimulating G i2 -coupled P2Y12 receptors.…”
Section: Figurementioning
confidence: 99%